Individual Patient Research (IPR) Outcomes with Alzheimer's Disease: The Psycho-neuro-immune Viewpoint - Chiappelli, Francesco (Bioinformation, 2016)
Traditional research in the health sciences has involved control and experimental groups of patients, and descriptive and inferential statistical analyses performed on the measurements obtained from the samples in each group. As the novel model of translational healthcare, which integrates translational research and translational effectiveness, becomes increasingly established in modern contemporary medicine, healthcare continues to evolve into a model of care that is evidence-based, effectiveness-focused and patientcentered. Patient-centered care requires the timely and critical development and validation of a new research paradigm, which is referred to as “individual patient research (IPR)”, as opposed as the customary group research approach. That is to say, research in geriatric disease conditions, such as Alzheimer’s Disease (AD) must be performed from the viewpoint of individual patient research outcomes, and individual patient data analysis. Here, we discuss IPR in patients with AD in the context of the best available research evidence that indicates psychological symptoms, endocrine deregulation, and immune alterations in AD. We propose a clinical adaptive cluster randomized stepped wedge blinded controlled trial, with sequential with sequential roll-out of an evidence-based intervention in a crossover paradigm.